2020
DOI: 10.1177/0272431620912490
|View full text |Cite
|
Sign up to set email alerts
|

Maladaptive Social Consequences of Emotional Clarity Deficits in Early Adolescence

Abstract: This study examined whether compromised emotional clarity prospectively contributes to maladaptive social behavior (aggression, anxious solitude) and adverse social experiences (low social status, victimization) in early adolescence; gender differences in these effects also were explored. Youth ( N = 636, [Formula: see text] age = 10.94, SD = 0.37) completed a self-report measure of emotional clarity in fifth grade, and their teachers completed measures of youth aggression, anxious solitude, social status, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Therefore, having a greater momentary understanding of one's emotions should facilitate adaptive social behavior. Prospective longitudinal studies further suggest that deficits in emotional clarity are linked to poorer social functioning and maladaptive social behavior among adolescents (Rudolph et al 2020). Two experience sampling studies (Thompson and Boden 2019;Tuck et al 2023) indicate that momentary emotional clarity is higher during prompts where participants also reported having social interactions.…”
Section: Social Situationsmentioning
confidence: 99%
“…Therefore, having a greater momentary understanding of one's emotions should facilitate adaptive social behavior. Prospective longitudinal studies further suggest that deficits in emotional clarity are linked to poorer social functioning and maladaptive social behavior among adolescents (Rudolph et al 2020). Two experience sampling studies (Thompson and Boden 2019;Tuck et al 2023) indicate that momentary emotional clarity is higher during prompts where participants also reported having social interactions.…”
Section: Social Situationsmentioning
confidence: 99%
“…In addition, results of available studies are mixed. In some studies, for girls only, cognitive reappraisal and expressive suppression were linked to depressive symptoms (Ogbaselase et al, 2022) and emotional clarity was linked to aggression and victimization (Rudolph et al, 2020). However, other studies found no gender differences in the strength of the links between emotional clarity and emotion regulation over time (Blöte & Westenberg, 2019;Flynn & Rudolph, 2014).…”
Section: Gender and Age Differences In Relations Between Emotion Regu...mentioning
confidence: 99%
“…Emotional clarity is associated with adaptive life outcomes, such as engaging in active and resourceful coping and developing self-affirming attributions for good events (Gohm & Clore, 2002). In contrast, low emotional clarity has been associated with poor emotional regulation (Gratz & Roemer, 2008), depression (Thompson et al, 2015) and maladaptive social behaviour such as aggression, victimization and bullying among female adolescents (García-Sancho et al, 2014; Rudolph et al, 2020).…”
Section: The Importance Of Emotional Claritymentioning
confidence: 99%
“…La claridad emocional está asociada con los resultados de la vida adaptativa, como puede ser afrontar una determinada situación de forma activa ingeniosa, y desarrollar atribuciones de auto-afirmación para acontecimientos positivos (Gohm & Clore, 2002). En contraste, la baja claridad emocional ha sido asociada con una deficiente regulación emocional (Gratz & Roemer, 2008), depresión (Thompson et al, 2015), y conducta social inadaptada, como por ejemplo agresión, victimización y acoso entre las adolescentes mujeres (García-Sancho et al, 2014; Rudolph et al, 2020).…”
Section: ¿Por Qué Ventilamos Nuestras Emociones Y Culpabilizamos a Ot...unclassified